National Standards for Psychological Literacy and Global Citizenship : Outcomes of Undergraduate Psychology Education : 2012 Final Report. - Cranney, Jacquelyn; Botwood, Lorayne; Morris, Sue (Office for Learning and Teaching, 2012)
Final report of a Teaching Fellowship at The University of New South Wales. The primary aim of this Fellowship was to engage stakeholders in psychology education in a review of the aims of the undergraduate degree program, and subsequently the expected learning outcomes and curriculum content. This Fellowship built on the outcomes of the author's previous ALTC Associate Fellowship, in particular the delineation of six graduate attributes for the Australian undergraduate psychology program (knowledge, research, critical thinking, values, communication, application). This report describes the author's further scholarly development of the concepts of psychological literacy and global citizenship, as well as the identification and implementation of strategies for translating these concepts into practice within the classroom.